2021
DOI: 10.1021/acs.energyfuels.1c03370
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Properties of Bitumen Froth from Oil Sands Surface Mining and Treatment of Water-in-Oil Emulsions

Abstract: Bitumen froth, as the crude product from the surface mining of oil sands, requires the efficient removal of water and solids for further processing. This work has systematically characterized the properties of bitumen froth from an oil sands operation in Northern Alberta and their correlation to the froth treatment efficiency (i.e., removal of water and demulsification behaviors). Systematic characterization was performed regarding the composition, wettability, and particle size distribution of the solids sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…2 This is followed by Wang and Zeng providing a systematic characterization of the properties of bitumen froth from an oil sands operation in Northern Alberta and probing their correlation to the froth treatment efficiency. 3 Parashkooh and Jian use data mining to guide molecular dynamics simulation of the coalescence of water-in-oil droplets. 4 Perez showed that demulsification efficiency of the asphaltene stabilizer does not correlate to the asphaltene inhibition performance but correlates better to the reduction in interfacial viscosity.…”
Section: ■ Emulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This is followed by Wang and Zeng providing a systematic characterization of the properties of bitumen froth from an oil sands operation in Northern Alberta and probing their correlation to the froth treatment efficiency. 3 Parashkooh and Jian use data mining to guide molecular dynamics simulation of the coalescence of water-in-oil droplets. 4 Perez showed that demulsification efficiency of the asphaltene stabilizer does not correlate to the asphaltene inhibition performance but correlates better to the reduction in interfacial viscosity.…”
Section: ■ Emulsionsmentioning
confidence: 99%
“…Salager, Marquez, Forgiarini, and co-workers reviewed the application of hydrophilic–lipophilic deviation (HLD) in water–oil emulsion from 30 years of research . This is followed by Wang and Zeng providing a systematic characterization of the properties of bitumen froth from an oil sands operation in Northern Alberta and probing their correlation to the froth treatment efficiency . Parashkooh and Jian use data mining to guide molecular dynamics simulation of the coalescence of water-in-oil droplets .…”
Section: Emulsionsmentioning
confidence: 99%